2021
DOI: 10.1021/acsomega.1c00241
|View full text |Cite
|
Sign up to set email alerts
|

Adrenic Acid-Derived Epoxy Fatty Acids Are Naturally Occurring Lipids and Their Methyl Ester Prodrug Reduces Endoplasmic Reticulum Stress and Inflammatory Pain

Abstract: Adrenic acid (AdA, 22:4) is an ω-6 polyunsaturated fatty acid (PUFA), derived from arachidonic acid. Like other PUFAs, it is metabolized by cytochrome P450s to a group of epoxy fatty acids (EpFAs), epoxydocosatrienoic acids (EDTs). EpFAs are lipid mediators with various beneficial bioactivities, including exertion of analgesia and reduction of endoplasmic reticulum (ER) stress, that are degraded to dihydroxy fatty acids by the soluble epoxide hydrolase (sEH). However, the biological characteristics and activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Adrenic acid, the immediate precursor derived from arachidonic acid, is necessary for neuronal development and enrichment of myelinic lipids ( 63 , 64 ). Adrenic acid is metabolized by cytochrome P450s to a group of epoxy fatty acids and epoxyeicosatrienoic acids, which are the vital lipid mediators playing key role in exerting analgesia and reducing endoplasmic reticulum stress ( 65 ). Furthermore, functional studies showed that adrenic acid potently inhibited the formation of the chemoattractant leukotriene B4 (LTB4), which has been proposed as a contributor for chronic neuroinflammatory effects ( 66 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adrenic acid, the immediate precursor derived from arachidonic acid, is necessary for neuronal development and enrichment of myelinic lipids ( 63 , 64 ). Adrenic acid is metabolized by cytochrome P450s to a group of epoxy fatty acids and epoxyeicosatrienoic acids, which are the vital lipid mediators playing key role in exerting analgesia and reducing endoplasmic reticulum stress ( 65 ). Furthermore, functional studies showed that adrenic acid potently inhibited the formation of the chemoattractant leukotriene B4 (LTB4), which has been proposed as a contributor for chronic neuroinflammatory effects ( 66 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adrenic acid (ADA; 22:4 ω 6) is an ω-6 FA more concentrated in liver, vasculature, kidney, adrenal gland, and brain. It can be converted into arachidonic acid through β-oxidation, which play an important role in inflammatory responses 57 , 59 , 60 . The plasma ADA concentration increases in humans and mice affected by nonalcoholic fatty liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…DiHODE is a degradation compound of epoxy-fatty acid 50 , which is positively associated with inflammation in other studies 51 . Since epoxide hydrolases can generate DiHODE from the corresponding epoxy-fatty acid 52 , this enzyme might be important in mediating the influences from lifestyle factors to cancer. DiHODE is also an oxylipin, which is influenced by a high fat diet 53 .…”
Section: Amn Identifies Inflammation Linking Lifestyle Factors To Bre...mentioning
confidence: 99%